Moving Matters : Paths of Serial Migration. - Ossman, Susan (Stanford University Press, 2013)
Moving Matters is a richly nuanced portrait of the serial migrant: a person who has lived in several countries, calling each one at some point ""home."" The stories told here are both extraordinary and increasingly common. Serial migrants rarely travel freely-they must negotiate a world of territorial borders and legal restrictions-yet as they move from one country to another, they can use border-crossings as moments of self-clarification. They often become masters of settlement as they turn each country into a life chapter. Susan Ossman follows this diverse and growing pop.